Facile synthesis of anatase/rutile TiO2/g-C3N4 multi-heterostructure for efficient photocatalytic overall water splitting. (10th July 2020) - Fang, Yuxuan; Huang, Wenxin; Yang, Siyuan; Zhou, Xunfu; Ge, Chunyu; Gao, Qiongzhi; Fang, Yueping; Zhang, Shengsen
Abstract: Rational design of high-efficiency heterostructure photocatalyst is an effective strategy to realize photocatalytic H2 evolution from pure water, but remains still a considerable challenge. Herein, an anatase/rutile TiO2 /g-C3 N4 (A/R/CN) multi-heterostructure photocatalyst was prepared by a facile thermoset hybrid method. The combination of two type-II semiconductor heterostructures (i.e., A/R and R/CN) significantly improve the separation and transfer efficiency of photogenerated carriers of anatase TiO2, rutile TiO2 and g-C3 N4, and A/R/CN photocatalyst with high activity is obtained. The optimal A/R/CN photocatalyst exhibits significantly increased photocatalytic overall water splitting activity with a rate of H2 evolution of 374.2 μmol g −1 h −1, which is about 8 and 4 times that of pure g-C3 N4 and P25. Moreover, it is demonstrated to be stable and retained a high activity (ca. 91.2%) after the fourth recycling experiment. This work comes up with an innovative perspective on the construction of multi-heterostructure interfaces to improve the overall photocatalytic water splitting performance. Graphical abstract: Image 1 Highlights: Anatase/rutile TiO2 /g-C3 N4 (A/R/CN) multi-heterostructure was prepared. The heterostructure can effectively separate and transfer photogenerated carriers. The A/R/CN hybrids exhibite efficient photocatalytic overall water splitting. The A/R/CN shows excellent stability and reusability.